Ameliorative effects of pirfenidone in chronic kidney disease - Samad Ghodrati; Yeganeh Ragati Haghi; Jyoti Baharani; Akshaya Joseph; Niloufar Alimohammadi; Farzad Koosha; Leila Mostafavi; Aiyoub Pezeshgi (Society of Diabetic Nephropathy Prevention, 2022)
Renal fibrosis is the hallmark of advanced chronic kidney disease (CKD), which is characterized by excessive accumulation of extracellular matrix (ECM) proteins and plays a central role in the pathogenesis and progression of CKD to end-stage renal disease (ESRD). The molecular and cellular substances of kidney fibrosis include growth factors, such as fibroblast growth factor (FGF), transforming growth factor beta (TGF-β) and platelet-derived growth factor (PDGF), alongside cytokines (like interleukin-1b) and metalloproteinases. Therefore, these factors can be evaluated as possible targets for anti-fibrotic agents. Among the mediators of fibrosis, TGF-β is the dominant facilitator of renal fibrosis that induces ECM construction and accumulation. Numerous studies have focused on the inhibition of TGF-β and its downstream targets for the treatment of renal disease. Abolition of TGF-β mRNA expression was found to be the mechanism of anti-fibrotic drug, pirfenidone, in the heart and kidneys of diabetic rats. Various investigations have shown the impact of pirfenidone in diminishing kidney fibrosis, with studies containing patients diagnosed with subtotal nephrectomy, diabetic kidney disease and unilateral ureteral obstruction (UUO), administered drugs such as cyclosporine, tacrolimus, doxorubicin and vanadate. Several therapeutic drugs for fibrosis reduce only one of the oxidative, inflammatory or profibrogenic markers, while pirfenidone targets all three of these markers and therefore, seems to be a particularly valuable drug.